Epoxidized Palm Kernel Oil and Monomethylol Urea as Co-Polymer Binder for a Water-Resistant Paint - S, Archibong C.; A, Thliza B.; G, Fadawa F.; T, Akaakondo F. (Darul Yasin Al Sys, 2025)
The development of eco-friendly and efficient binders remains a critical focus in modern paint formulation. In this study, the triglyceride structure of palm kernel oil was epoxidized and structurally modified to create reactive sites for chemical bonding. The resulting epoxidized palm kernel oil (EPKO) was chemically blended with monomethylol urea (MMU), a thermoset resin obtained from one-step condensation polymerization of urea and formaldehyde to produce a hybrid copolymer composite (EPKO/MMU). Structural characterization using Fourier Transform Infrared Spectroscopy (FTIR) confirmed chemical interactions between EPKO and MMU, evidenced by upward and downward shifts in absorption bands. Rheological evaluation revealed enhanced film-forming properties. Viscosity, refractive index, elongation at break, and turbidity increased with higher EPKO content up to 50%, after which deviations were observed. Conversely, melting point, density, formaldehyde emission, and moisture uptake decreased with continuous EPKO incorporation. The hybrid copolymer successfully combined the advantages of both components, mitigating the rigidity and high formaldehyde emission of MMU while enhancing flexibility, hydrophobicity, and water resistance contributed by EPKO. The findings demonstrate the potential of EPKO/MMU composites as sustainable, high-performance binders for emulsion paint applications, offering improved environmental compatibility and superior material properties.